Water consumption and preliminary crop coefficients of two Populus ×canadensis clones (‘I-214’ and ‘I-488’) grown at low planting density - Cañete Salinas, Paulo (2021)
Aim of study: The productivity of poplar plantations in Mediterranean climates might be reduced due to lower precipitations in a climate change scenario. Therefore, understanding the water consumption in these plantations is essential for their management. The objective of this study was to estimate water consumption and preliminary crop coefficients (kc) of two universally used poplar clones (Populus x Canadensis ‘I-214’ and ‘I-488’). Area of study: Central Chile (36º 05 'LS; 72º 47' LW; 470 m.a.s.l.). Materials and methods: Commercial stands of poplar clones established in 2009 and 2010 at low density (6×6 m) were used to experiment during the 2016-2017 growing season. In each of them, water balance was measuring, by determining evaporation using micro lysimeters and transpiration using the sap flow. Additionally, the water status and the leaf area index (LAI) were measured to understand the behaviour of both clones. Main results: Although the water supplied to both clones was the same, the transpiration (T) was higher for ‘I-488’ than ‘I-214’, at those moments in which the evapotranspiration (ETr) and the vapour pressure deficit (VPD) was higher. On the other hand, differences were observed in plant water status, ‘I-488’ had more negative xilematic water potential (Ψx) compared to ‘I-214’. In turn, I-214 proved to have a higher Leaf Area Index (LAI) than I-488 and grew more during the season, refuting its greater efficiency. Research highlights: These results allow characterizing the water behaviour of both clones in Mediterranean climate condition, but it is necessary to extend the study to more seasons and different age ranges.